Fluxos e níveis de conhecimento na gestão dos convênios do departamento de oftalmologia de UNIFESP - Barbosa, Beatriz Candida [UNIFESP] (2016)
Researchers need to know how to raise funds and provide public and private funding to efficiently manage their projects. This study aims to verify the knowledge of the researchers of the Department of Ophthalmology and Visual Sciences of the Paulista School of Medicine - UNIFESP about fundraising and accountability in public and private instances and Training and training to use these (the individual himself, The institution or department of origin). The included population consisted of 16 volunteers distributed among project coordinators, responsible for accountability of covenants, and expense officers of the selected department. This selection was due to the convenience of the researcher. The methodology used was the application of a questionnaire, prepared for this study to evaluate the opinion of the researchers about their knowledge about the determinations provided in the legislations of the State, Municipal, Federal and other organs of development that must follow a specific law through agreements Agreed with the Department / University. The questionnaires were sent to 23 supervisors of a postgraduate program of the selected department and returned 16. The results obtained through the 16 questionnaires were tabulated for: experience in fundraising, knowledge of resource use rules, and As to who is entitled to the training and training to use these (the individual, the institution or department of origin). In the sample, 68.75% of statutory volunteers were identified, and the others were distributed among the clerk (12.5%) and others (01 affiliated teachers and 02 unresponsive teachers). The working time experience of most of the volunteers was 10 years or higher, being 87.5% in the department and 75% in UNIFESP. In terms of fundraising, all of them had experience in at least one type of institution, including private ones (Abbot, Summit, Rotary Club, Pharmaceutical Industry, American Enterprise), among them public (Federal- CAPES, FNS, CNPQ, Ministry of Health and State - FAPESP) , Bayer). With regard to the knowledge of resource use rules of project preparation, 10 responses were fully found (62.5%), 05 responses reasonably (31.25%) and only one response is unknown. Regarding the training and training on the agreements, there was a consensus that it should exist, being the responsibility of the development agencies and / or university. It is worth mentioning that there is an ignorance of the respondents about the services provided by UNIFESP in the agreement department (43.75%); As well as the analysis department of accounts / contracts and agreements (43.75%); And budget management department (68.75%). Regarding accountability, the majority replied that they know fully or reasonably. However, there was a high occurrence of ignorance about the competence and attributions of the external control bodies such as the General Comptroller of the Union and the Federal Audit Court that carry out the external supervision of the proper application of public resources. There was a lack of knowledge about the existence of some internal departments of UNIFESP (budget department, accountability analysis department, department of agreements and Permanent Process Commission). In conclusion, the researchers are aware of the processes for managing agreements, but are unaware of the existence of UNIFESP internal departments (budget department, accountability analysis department and covenants department) that could help with doubts about project design and delivery. accounts. Given the results obtained, the final product of this study will be the preparation of a primer containing the basic information necessary to assist the researcher in the management of his / her covenant.